HBR's 10 must reads on entrepreneurship and startups - Sahlman, William Andrews,; Hoffman, Reid,; Andreessen, Marc,; Blank, Steven G.; Blank, Steven G. (HBR's 10 must reads (Series), 2018)
The best entrepreneurs balance brilliant business ideas with a rigorous commitment to serving their customers' needs. If you read nothing else on entrepreneurship, read these 10 articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you build your company for enduring success. Leading experts and practitioners such as Clayton Christensen, Marc Andreessen, Steve Blank, and Reid Hoffman provide the insights and advice you need to: Build a business from the ground up Adopt lean startup practices like business model experimentation Be realistic about how prescient your business plan can truly be Focus on the most important part of your business: the people Connect powerfully with your audience of investors and customers - Understand where companies with the most impact are launching now--